Black Shale Paleo-Environmental Reconstructions: A Geochemical Case Study of Two Ordovician–Silurian Boundary Sections in Middle Yangtze Area, China - Yi, Xuefei; Ji, Xia; Huang, Yunfei; Liu, Zuosong; Meng, Jianghui (Frontiers in Earth Science, 2022)
Under the promotion of exploration and development for shale oil and gas, marine shale has become a hotspot of fine-grained sedimentary studies in China. Paleo-environment reconstruction has always been an important aim, especially for black shale. Based on a large number of samples collected from Wufeng and Longmaxi Formations of two field sections in western Hubei and eastern Chongqing, this study compares the vertical variations in total organic carbon content, quartz/clay mineral value, and trace element compositions of these two profiles to reflect the paleo-environment changes from the latest Ordovician to the earliest Silurian. The results show that during the later Ordovician period, when Wufeng Formation deposited, the study area experienced a water depth change from relative deep facies to shallow marine, and paleo-redox changed from oxygen rich to anoxic, and even euxinic, followed by the content of oxygen increase. When the Guanyinqiao Bed deposited, the basin suddenly became shallower, and the deposition environment changed to be oxygen enriched for high water energy, circulating oxygen enriched. In the earliest stage Silurian, when the Longmaxi Formation formed, and the paleo-water also suffered several changes of sea level, and the paleo-environment also changed from anoxic to oxic. These changes can correspond to the third-forth order sequences well.